2020
DOI: 10.1111/nan.12659
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield pathologic burden in Lewy body diseases vs. Alzheimer’s disease

Abstract: Lewy body diseases (LBD) are characterized by alpha‐synuclein (SYN) pathology, but co‐morbid Alzheimer’s disease pathology is common and the relationship between these pathologies in microanatomic hippocampal subfields is understudied. Here, we use digital histological methods to measure the distribution, severity, and association of alpha‐SYN, tau, and amyloid‐β pathology in hippocampla subfields in LBD and Alzheimer's disease subjects. We also correlate pathologic burden with antemortem episodic memory testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 75 publications
5
23
2
Order By: Relevance
“…The noradrenergic LC system often becomes degenerated early in both alpha-synucleinopathies such as Parkinson's disease (PD) (Solopchuk et al, 2018;Li et al, 2019), and ß-amyloidopathies like Alzheimer's disease (AD) (Zarow et al, 2003;Hou et al, 2021). Both diseases are closely related to Lewy body pathology, as mixed pathologies can coexist in patients with cognitive impairment (Coughlin et al, 2020). Lewy body dementia includes the terms PD dementia and DLB (Haider et al, 2020).…”
Section: Degeneration Of the Locus Coeruleus In Dementia With Lewy Bomentioning
confidence: 99%
See 2 more Smart Citations
“…The noradrenergic LC system often becomes degenerated early in both alpha-synucleinopathies such as Parkinson's disease (PD) (Solopchuk et al, 2018;Li et al, 2019), and ß-amyloidopathies like Alzheimer's disease (AD) (Zarow et al, 2003;Hou et al, 2021). Both diseases are closely related to Lewy body pathology, as mixed pathologies can coexist in patients with cognitive impairment (Coughlin et al, 2020). Lewy body dementia includes the terms PD dementia and DLB (Haider et al, 2020).…”
Section: Degeneration Of the Locus Coeruleus In Dementia With Lewy Bomentioning
confidence: 99%
“…There is another prodromal DLB subtype besides psychiatric prodromal DLB that is characterized by mild cognitive impairment (McKeith et al, 2020 ). Episodic memory dysfunction exists in DLB, and might be related to the spread of alpha synuclein pathology in hippocampal subfields CA2/3 (Coughlin et al, 2020 ) as relevant structures for memory formation. Furthermore, Coughlin et al ( 2020 ) demonstrated that hippocampal tau protein within the hippocampus subregion CA2/3 correlated negatively with memory function in patients with LBD.…”
Section: Noradrenergic Mechanisms Inducing Psychiatric Symptoms In Prmentioning
confidence: 99%
See 1 more Smart Citation
“…While in AD, amyloid beta (Aβ), and tau play a central role, in DLB and PD -synuclein ( -syn) is a key mediator [2][3][4][5][6] . However, -syn has been shown to accumulate in the brains during aging and in AD and in DLB, Aβ and tau are also found in conjunction with -syn in selected brain regions [7][8][9] .…”
Section: Introductionmentioning
confidence: 99%
“…Suspected DLB patients exhibit a neuropsychological profile suggesting Lewy Body pathology, such as visuospatial deficits or attentional executive dysfunction with relatively intact episodic memory function. Though some DLB patients also show memory deficits ( Coughlin et al, 2020 ), which makes it difficult to distinguish them from patients with Alzheimer dementia. To diagnose DLB according to McKeith’s criteria ( McKeith et al, 2017 ), the patients must display a progressive dementia interfering with daily living activities.…”
Section: Introductionmentioning
confidence: 99%